Application of Amorphous Calcium Phosphate Agents in the Prevention and Treatment of Enamel Demineralization - Yan, Jiarong; Yang, Hongye; Luo, Ting; Hua, Fang; He, Hong (Frontiers in Bioengineering and Biotechnology, 2022)
Enamel demineralization, as a type of frequently-occurring dental problem that affects both the health and aesthetics of patients, is a concern for both dental professionals and patients. The main chemical composition of the enamel, hydroxyapatite, is easy to be dissolved under acid attack, resulting in the occurrence of enamel demineralization. Among agents for the preventing or treatment of enamel demineralization, amorphous calcium phosphate (ACP) has gradually become a focus of research. Based on the nonclassical crystallization theory, ACP can induce the formation of enamel-like hydroxyapatite and thereby achieve enamel remineralization. However, ACP has poor stability and tends to turn into hydroxyapatite in an aqueous solution resulting in the loss of remineralization ability. Therefore, ACP needs to be stabilized in an amorphous state before application. Herein, ACP stabilizers, including amelogenin and its analogs, casein phosphopeptides, polymers like chitosan derivatives, carboxymethylated PAMAM and polyelectrolytes, together with their mechanisms for stabilizing ACP are briefly reviewed. Scientific evidence supporting the remineralization ability of these ACP agents are introduced. Limitations of existing research and further prospects of ACP agents for clinical translation are also discussed.